PELATIHAN PENULISAN KARYA TULIS ILMIAH UNTUK MENINGKATKAN KOMPETENSI SISWA SMAN 1 KRAKSAAN - Onny Fransinata Anggara; Nurchayati Nurchayati; Ni Wayan Sukmawati Puspitadewi (Program Studi S1, S2, S3 Mananajemen Pendidikan Universitas Negeri Surabaya, 2023)
Writing scientific articles is writing whose editing is based on scientific studies that have a certain scientific basis. The presentation of scientific work must be systematic, logical and careful in all respects. The purpose of the scientific paper writing training activities is to foster interest, enthusiasm, and creative and innovative ideas from students off SMAN 1 Kraksaan to produce scientific work in accordance with the rules of writing. Furthermore, it can improve the competence of students which includes the ability to think critically, creatively, communicatively and collaboratively. Based on the results of the implementation of the training activities, it can be concluded that the activities went well and received full support from the school. All training participants took part in the activity until the end with an attendance rate of 100%. The activity participants were enthusiastic to ask questions, explore ideas, and express opinions. Thus, in the future, it is hoped that there will be further activities involving accompanying teachers to optimize their role in preparing scientific papers for students.